Excessive daytime sleepiness in asthma: What are the risk factors?. (3rd August 2018) - Kallin, Sandra Andersson; Lindberg, Eva; Sommar, Johan Nilsson; Bossios, Apostolos; Ekerljung, Linda; Malinovschi, Andrei; Middelveld, Roelinde; Janson, Christer
ABSTRACT: Objective : Previous studies have found that excessive daytime sleepiness (EDS) is a more common problem in asthmatic subjects than in the general population. The aim of this study was to investigate whether the prevalence of EDS is increased in asthmatic subjects and, if so, to analyse the occurrence of potential risk factors for EDS in asthmatics. Methods : Cross-sectional epidemiological study. In 2008, a postal questionnaire was sent out to a random sample of 45, 000 individuals aged 16–75 years in four Swedish cities. Results : Of the 25, 160 persons who participated, 7.3% were defined as having asthma. The prevalence of EDS was significantly higher in asthmatic subjects (42.1% vs. 28.5%, p < 0.001) compared with non-asthmatic subjects. Asthma was an independent risk factor for EDS (adjusted OR 1.29) and the risk of having EDS increased with asthma severity. Risk factors for EDS in subjects with asthma included insomnia (OR, 3.87; 95% CI, 3.10–4.84); chronic rhinosinusitis (OR, 2.00; 95% CI, 1.53–2.62); current smoking (OR, 1.60; 95% CI, 1.15–2.22) and obesity (OR, 1.53; 95% CI, 1.09–2.13). Conclusions : EDS is a common problem among subjects with asthma. Asthma is an independent risk factor for having EDS. Furthermore, subjects with asthma often have other risk factors for EDS, many of them potentially modifiable.